RECLAMATION OF WASTE LUBRICATING OILS USING GROUND PERIWINKLE SHELL ADSORBENTS (Biological Sciences - PJSIR, 2004)
Acid treated ground periwinkle (Fuscatus tympanotonu) shell adsorbents were used in the reclamation of used hydraulic oil by both the continuous elution and bed filtration techniques.Quantitative yields of oils were obtained by both tech- niques. The bed filtration technique gave clear oils but was slower than the continuous elution technique. Comparison with conventional adsorbents showed that the ground shell adsorbent was comparable to fullers earth and better than silica or alumina. Elevated temperature oxidation of the reclaimed oils in the presence of atmospheric oxygen gave resins, which could be used in the production of paints, leather polishes and wood varnishes.